Recombinant LH supplementation in patients with a relative reduction in LH levels during IVF/ICSI cycles: A prospective randomized controlled trial. (March 2017) - Lahoud, Robert; Ryan, John; Illingworth, Peter; Quinn, Frank; Costello, Michael
Abstract: Purpose: The aim of this study was to assess the use of recombinant luteinizing hormone (rLH) supplementation in patients who experience a reduction in LH concentration during controlled ovarian hyperstimulation (COH) for IVF/ICSI. Methods: A multi-center prospective randomized controlled trial (RCT) was performed over three years. Two hundred and forty patients aged between 24 and 42 years undergoing IVF/ICSI treatment with a long down regulation (LDR) protocol were recruited. LH was measured on the day FSH was started and again 6 days later. 100 patients had a 50% or greater reduction in LH levels and these were randomized to receive either recombinant LH (rLH) supplementation (group 1, n = 43) or no additional rLH supplementation (group 2, n = 57). Group 1 received rLH 75IU daily from day 7 of FSH stimulation to the day of HCG trigger. Results: There were no differences in either live birth or clinical pregnancy rates per embryo transfer between the two groups (27.8% vs. 37.0%, p = 0.39, RR = 0.75, 95%CI 0.39–1.44 and 36.1% vs. 43.5% p = 0.51, RR = 0.84, 95%CI 0.5–1.48, respectively). Conclusion: In conclusion the addition of rLH in patients with a relative reduction in serum LH concentration during COH for IVF/ICSI did not improve live birth or clinical pregnancy rates. However the results were not conclusive and further large well-designed RCTs are required to confirm these findings.